Acoustofluidic devices controlled by cell phones. Issue 3 (5th January 2018) - Bachman, Hunter; Huang, Po-Hsun; Zhao, Shuaiguo; Yang, Shujie; Zhang, Peiran; Fu, Hai; Huang, Tony Jun
Abstract : A portable control system consisting of a cell phone and a portable Bluetooth® speaker is presented to wirelessly control sharp-edge-based acoustofluidic devices. Abstract : Acoustofluidic devices have continuously demonstrated their potential to impact medical diagnostics and lab-on-a-chip applications. To bring these technologies to real-world applications, they must be made more accessible to end users. Herein, we report on the effort to provide an easy-to-use and portable system for controlling sharp-edge-based acoustofluidic devices. With the use of a cell phone and a modified Bluetooth® speaker, on-demand and hands-free pumping and mixing are achieved. Additionally, a novel design for a sharp-edge-based acoustofluidic device is proposed that combines both pumping and mixing functions into a single device, thus removing the need for external equipment typically needed to accomplish these two tasks. These applications serve to demonstrate the potential function that acoustofluidic devices can provide in point-of-care platforms. To further this point-of-care goal, we also design a portable microscope that combines with the cell phone and Bluetooth® power supply, providing a completely transportable acoustofluidic testing station. This work serves to bolster the promising position that acoustofluidic devices have within the rapidly changing research and diagnostics fields.